Project Based Learning: An Attempt To Develop Student'S Academic Writing Skills - Nur Shabrina Reznani; Bambang Sulistyo; Nurhasanah Nurhasanah (Pedagogi: Jurnal Ilmu Pendidikan, 2022)
This study aims to see the effectiveness of project based learning on the academic writing skills of STIE Dwi Sakti Baturaja students. The research method used in this study was a pre-experiment with a research design of One Group Pretest-Posttest Design. The sample of this study amounted to 60 students. The data collection technique used a test technique which was divided into pretest and posttest. The data processing technique used a t-test calculation with the SPSS 20 program. The results showed that project based learning was effective on students' academic writing skills. Furthermore, students who can improve their score at least 10 points better than the score they get from the initial test with a score above 90 there are 11 students. Furthermore, students who have a score of more than 78 there are 14 students. A total of 35 students got a minimum score of 78 after using PBL in their writing activities.